Molecularly Imprinted Polymer-Supported Ceramic Catalysts for Environmental Applications: A Comprehensive Review - Mateus Aquino Gonçalves; Felipe de Almeida la Porta; Adilson Candido da Silva; Teodorico Castro Ramalho; Sérgio Francisco de Aquino (Ceramics, 2025)
Molecularly imprinted polymers (MIPs) are synthetic polymers designed to exhibit selective recognition and binding capabilities toward target molecules and have been widely combined with advanced ceramic-based materials toward better performance in many catalytic applications of interest and beyond. What sets MIPs apart is their molecularly imprinted cavities, which are formed during polymerization in the presence of a template molecule. Upon template removal, these cavities retain the shape, size, and chemical functionality of the template molecule, allowing for highly specific recognition and binding of target molecules. In recent years, there has been a growing interest in leveraging these molecularly imprinted cavities not only for molecular recognition and sensing but also as catalytic sites and supports. Complementary to experimental studies, density functional theory (DFT) calculations are increasingly used to elucidate the molecular interactions, catalytic mechanisms, and optimize the design of MIP–ceramic catalysts. This review aims to provide a comprehensive overview of the current state of research on advanced ceramic-based catalysts supported by MIPs for environmental applications. Additionally, the review will discuss challenges and future directions in the field, focusing on enhancing the catalytic efficiency, stability, and scalability of MIP-based ceramic catalysts. By exploring these aspects, this review seeks to illustrate the promising role of MIP-modified ceramic materials in advancing the field of catalysis and catalytic supports.